Jesus and the cross: reflections of Christians from Islamic contexts - Singh, David Emmanuel (Global theological voices, 2008)
The Cross reminds us that the sins of the world are not borne through the exercise of power but through Jesus Christ's submission to the will of the Father. The papers in this volume are organised in three parts: scriptural, contextual and theological. The central question being addressed is: how do Christians living in contexts, where Islam is a majority or minority religion, experience, express or think of the Cross?